Whole Genome Sequencing of the Braconid Parasitoid Wasp Fopius arisanus, an Important Biocontrol Agent of Pest Tepritid Fruit Flies. Issue 8 (1st August 2017) - Geib, Scott M; Liang, Guang Hong; Murphy, Terence D; Sim, Sheina B
Abstract: The braconid wasp Fopius arisanus (Sonan) is an important biological control agent of tropical and subtropical pest fruit flies, including two important global pests, the Mediterranean fruit fly ( Ceratitis capitata ), and the oriental fruit fly ( Bactrocera dorsalis ). The goal of this study was to develop foundational genomic resources for this species to provide tools that can be used to answer questions exploring the multitrophic interactions between the host and parasitoid in this important research system. Here, we present a whole genome assembly of F. arisanus, derived from a pool of haploid offspring from a single unmated female. The genome is ∼154 Mb in size, with a N50 contig and scaffold size of 51, 867 bp and 0.98 Mb, respectively. Utilizing existing RNA-Seq data for this species, as well as publicly available peptide sequences from related Hymenoptera, a high quality gene annotation set, which includes 10, 991 protein coding genes, was generated. Prior to this assembly submission, no RefSeq proteins were present for this species. Parasitic wasps play an important role in a diverse ecosystem as well as a role in biological control of agricultural pests. This whole genome assembly and annotation data represents the first genome-scale assembly for this species or any closely related Opiine, and are publicly available in the National Center for Biotechnology Information Genome and RefSeq databases, providing a much needed genomic resource for this hymenopteran group.